Summary to the Plant Theory - Scholten, Jan (Homœopathic Links, 2017)
This article is a summary of ‘Introduction to the Plant Theory’ published in LINKS 2/2017. It describes the application of the theory with the use of the Remedy code.
Keywords: Plant Theory; Plant kingdom; Remedy code; Botany; APG classification